Force-slip-displacement of fiber cemboard panels subjected to four-point bending test - Nur Amirah Najwa, Mohammed; Arnie Farhana, Norhalim; Zainorizuan, Mohd Jaini; Mazlan, Abu Seman (Penerbit UTHM, 2022)
For many years, fibre cemboard has been widely used in the construction industry. This material has many advantages, including a long-life span, ease of installation and low maintenance, which can reduce the cost of maintenance. However, due to its limitation of being unable to support heavy loads, it is only suitable for the lightweight floor system. Therefore, the fibre cemboard panel is introduced. Basically, the fibre cemboard panel consists of several layers of fibre cemboard that stack together using a special bond mechanism. This study aims to investigate the flexural capacity and slip displacement of fibre cemboard panels with different bond mechanisms (polyurethane glue, steel bolts and polyurethane glue + steel bolts) and spacings (50 mm, 75 mm, 100 mm, 150 mm, and 200 mm). The specimens were fabricated with a size of 305 mm width, 1220 mm span and 2@16 thickness. The four-point bending test was carried out using Universal Testing Machine (UTM) that yield the force-slip displacement curves. The results of experimental testing indicate that the bond mechanism has an apparent impact on the flexural capacity and slip displacement. The fibre cemboard panels bonded by steel bolts have the best performance. Meanwhile, the spacing was found to control the slip displacement the most than the flexural capacity. Close distance of spacing may increase the stiffness that appreciably contributes to better performance. The optimum spacing for the polyurethane glue is 50 mm, while the specimens bonded by steel bolts and polyurethane glue + steel bolts should have 75 mm and100 mm spacings. The polyurethane glue can hold the stress concentration before the detachment. When polyurethane glue fails, the steel bolts resume the function to resist the slip displacement until the rapture.